Spectrophotometric Studies of Various Fe(III)-Substituted Aminothiophenol Systems - Chakravarty, V.P.; Deshpande, Y.H. (Asian Journal of Chemistry, 2010)
The complex formation process between Fe(III) and various substituted aminothiophenols has been investigated spectrophotometrically and formation of fairly stable complexes inferred. The complexes absorb at 460 and 470 nm.